ChemInform Abstract: Nucleoside Azide—Alkyne Cycloaddition Reactions under Solvothermal Conditions or Using Copper Vials in a Ball Mill. Issue 35 (September 2015) - Vyle, Joseph S.; et al.
Abstract Solution‐phase conditions and vibration ball milling to effect the preparation of triazole‐linked photoswitchable nucleosides like (III) are compared.